2008
DOI: 10.4000/emscat.1482
|View full text |Cite
|
Sign up to set email alerts
|

Introduction

Abstract: Les auteurs précisent que leur livre « pose des questions qui ont intéressé l'anthropologie sociale » en citant les travaux de Jack Goody (1962) sur les règles selon lesquelles la propriété du défunt se transmet à ses descendants dans deux villages de la Volta Noire, et ceux de Maurice Bloch (1971) sur la relation aux morts à travers les sépultures chez les Merina de Madagascar. Dans un travail fondateur, Maurice Bloch a en effet étudié la place des morts dans l'organisation sociale et l'activité économique de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
0
6
0
2
Order By: Relevance
“…My own conversations with Dörvöd herder-hunters, diviners, and monks in Uvs province confirmed that the protocol followed to choose, request, and take a place for funerary purposes is roughly similar today, despite the upheavals caused in Mongolian funerary practices by the 1950s reform, officially forbidding the practice of laying out the dead in the open. To begin with, and as I have shown elsewhere, the practice of laying out in the open was never completely abandoned throughout the socialist period, and has even regained prominence in Mongolia since the abrogation of funerary laws at the beginning of the 1990s (Delaplace 2008;Delaplace and Legrain 2021). As a result, herder-hunters in Tarialan or Ömnögovi districts still perform these protocols out in the mountains, whenever they are instructed by a lama or diviner to lay out a dead parent there.…”
Section: O F H O R S E S a N D G R Av E S I T E Smentioning
confidence: 99%
See 1 more Smart Citation
“…My own conversations with Dörvöd herder-hunters, diviners, and monks in Uvs province confirmed that the protocol followed to choose, request, and take a place for funerary purposes is roughly similar today, despite the upheavals caused in Mongolian funerary practices by the 1950s reform, officially forbidding the practice of laying out the dead in the open. To begin with, and as I have shown elsewhere, the practice of laying out in the open was never completely abandoned throughout the socialist period, and has even regained prominence in Mongolia since the abrogation of funerary laws at the beginning of the 1990s (Delaplace 2008;Delaplace and Legrain 2021). As a result, herder-hunters in Tarialan or Ömnögovi districts still perform these protocols out in the mountains, whenever they are instructed by a lama or diviner to lay out a dead parent there.…”
Section: O F H O R S E S a N D G R Av E S I T E Smentioning
confidence: 99%
“…Another more discreet, less known, and more contemporary way in which horses, as mor', are made to contribute to Mongolian funerals, however, is to detect the presence of invisible things at the gravesite. More specifically, saddled horses contribute to the process of 'requesting' and 'seizing a place' (gazar guih, gazar avah), most of all when laying Delaplace: A Concern for the Invisible: Dwelling with Sensitive Horses and Vanishing Graves in Mongolia a body out in the open as was the custom for commoners in Mongolia before the funerary reform of 1955 (Delaplace 2008). This process has been well described by Charles R. Bawden (1994aBawden ( [1977), on the basis of three different texts: one manuscript detailing "prayers" to be read and protocols to be performed when "requesting land" for a gravesite, the transcript of an interview of two elders by a colleague of the author's, and an excerpt from the autobiography of Jügderiin Damdin, published in 1973, where he described his grandmother's funeral in the first decades of the 20th century.…”
Section: O F H O R S E S a N D G R Av E S I T E Smentioning
confidence: 99%
“…Many studies have highlighted the power of uttered words in Mongolia (e.g. Delaplace 2009 a : 196‐209; Empson 2011: 86‐7; Hamayon 1971; Hamayon & Bassanoff 1973; Højer 2003: 81‐120; 2004: 50‐61; Legrain 2014 a : 288). There exists a triadic performative relation between a person, his/her fortune, and speech, which is maybe most evident in people's concerns about the choice of names.…”
Section: Power Of Speech and Economy Of Attentionmentioning
confidence: 99%
“…Otros, como los selk'nam, los cheyennenes, los siux y los !kung, suponen que, a la muerte, las personas han de alejarse a lugares remotos de los que casi nunca han de volver; y, si acaso llegaran reencontrarse con los vivos sólo será para atraer diversas clases de desgracias (véanse Gusinde 2008:111-157;Straus 1978;Hassrick 1993:17-23, 341-345, 246;Marshall 1999:27-30, 177-180;Woodburn 1982:195). Y otros más, como los aborígenes australianos, los inuit, los cree, los tlingit y los forrajeros siberianos, creen que, tras el fallecimiento, los seres humanos han de retornar a la vida como un miembro del mismo grupo pero en una próxima generación -sea por el intermedio de ancestros totémicos o por el de entidades zoológicas ligadas al bosque (véanse Spencer y Gillen 1904:145-150, 506-543;Moizo 1983;Thalbitzer 1930:93;Rasmussen 1931:220;Tanner 1979:148, 153, 172;Kan 1987:35;Hamayon 2010:42-51;Delaplace 2009;Lambert 2003). Lo relevante es que en todos estos pueblos los muertos, en condiciones habituales, sólo parecen existir transitoriamente; pues, ya sea que se esfumen en el medio, se dirijan a lugares remotos o se reciclen como nuevos humanos, éstos tienden a dejar de interactuar con los vivos o, en su defecto, devienen entidades a las que es preferible alejar.…”
Section: Entre Lo Visible Y Lo Invisibleunclassified